Quality Indicators for Small Bowel Capsule Endoscopy - Ki-Nam Shim; Seong Ran Jeon; Hyun Joo Jang; Jinsu Kim; Yun Jeong Lim; Kyeong Ok Kim; Hyun Joo Song; Hyun Seok Lee; Jae Jun Park; Ji Hyun Kim; Jaeyoung Chun; Soo Jung Park; et al. (Korean Society of Gastrointestinal Endoscopy, 2017)
Capsule endoscopy (CE) enables evaluation of the entire mucosal surface of the small bowel (SB), which is one of the most important steps for evaluating obscure gastrointestinal bleeding. Although the diagnostic yield of SB CE depends on many clinical factors, there are no reports on quality indicators. Thus, the Korean Gut Image Study Group (KGISG) publishes an article titled, "Quality Indicators for Small Bowel Capsule Endoscopy" under approval from the Korean Society of Gastrointestinal Endoscopy (KSGE). Herein, we initially identified process quality indicators, while the structural and outcome indicators are reserved until sufficient clinical data are accumulated. We believe that outcomes of SB CE can be improved by trying to meet our proposed quality indicators.